Assessment of the soft skills of the final degree students at UTB: A contrast between engineering and other faculties (2022)
The purpose of this research focuses on knowing the perception that end-of-career students of the engineering faculty have about the soft skills that constitute the institutional hallmark of the Technological University of Bolívar (UTB), in contrast to the assessment that given to them by students from other faculties. The study is exploratory in nature and used a cross-sectional qualitative research design. An instrument was designed and applied considering seven dimensions associated with the soft skills of the UTB seal, defining at least five (5) categories for each one. Through descriptive, correlational and inferential statistical analyses, it is evident that, for both engineering students and those from other faculties, the dimensions are not valued in the same way, but rather the appreciation is supported according to their training discipline. Based on the above, it is recommended that the university establish transversal strategies that contribute to the comprehensive recognition by students of all the dimensions that make up the institutional seal. © 2022 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.